Analysis of the Quality of the Work Environment and Nutritional Status on the Fatigue of Educators - Sahrir Sillehu; Zulfikar Lating; Ilyas Ibrahim; Abd. Rijali Lapodi (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Work fatigue is a criterion that concerns physical and psychological fatigue only, but has more to do with a decrease in physical performance, a feeling of fatigue, a decrease in motivation, and a decrease in work productivity. The purpose of this study was to measure the quality of the work environment (noise, lighting) and nutritional status of educators at the Maluku Husada High School of Health Sciences (STIkes). This research is a type of quantitative research with analytical and descriptive methods. The population in this study were 33 respondents and the sampling technique used was total sampling and cluster sampling. Data analysis was performed using correlation tests: Spearman Correlations and Mann-Whitney tests. The results of statistical tests using Spearman Correlations the effect of nutritional status on work fatigue obtained a p-value of 0.426 indicating that there is no effect between nutritional status and work fatigue. The conclusion is that there is an influence between the level of lighting on work fatigue. There is no effect between noise level and body mass index on work fatigue. Keywords ; Quality of Work Environment, Nutritional Status, Work Fatigue